O desenvolvimento psicológico do adulto com deficiência adquirida: contribuições de A. R. Luria na obra O homem com um mundo estilhaçado - Lopes, Eliza Maura Castilho; Leite, Lucia Pereira; Neme, Carmen Maria Bueno; Valle, Tânia Gracy Martins (Universidade Federal Fluminense, Departamento de Psicologia, 2016)
Abstract Acquiring a disability can result in major changes in an adult’s life. According to the Cultural-Historic Psychology, the individual development will continue to occur, taking into account his objective conditions. To explore how this development occurs and the role of Psychology towards the subjects who acquire a disability, this paper aims to analyze the book “The man with a shattered world,” of A. R. Luria, that tells the story of an adult who suffered a brain injury. The book will be discussed based on Luria’s theoretical premisses, and on others authors of the same theoretical approach, like Vigotski and Leontiev.

Resumo Adquirir uma deficiência pode implicar em importantes transformações na vida de um adulto. Segundo pressupostos da Teoria Histórico-Cultural, o desenvolvimento do indivíduo continuará ocorrendo, considerando suas condições objetivas. Para explorar como ocorre esse desenvolvimento e qual o papel da Psicologia enquanto ciência diante do sujeito que adquire uma deficiência, será analisado o livro “O homem com um mundo estilhaçado”, de A. R. Luria, que conta a história de um indivíduo adulto que sofre uma lesão cerebral. A obra será discutida com base em pressupostos teóricos do próprio Luria, e de teóricos da mesma abordagem, como Vigotski e Leontiev.
The psychological development of adults with acquired disabilities: contributions from A. R. Luria’s work The man with a shattered world
Keywords: disability; acquired disability; adult development; deficiência; deficiência adquirida; desenvolvimento do adulto